Drug discovery and development: a historical overview, current challenges and perspectives - Yu, Chai Xin; Tham, Chau Ling (Biome Scientia, 2024)
The evolution of drug discovery has proceeded for decades. The process has involved the invention of new theories, technologies, disciplines and medicines. These advancements play significant roles in drug discovery today as well as in the future. In this review, the important achievements of ancient Egyptian, Greek, Arabic, Indian, and Chinese medicines were discussed. Then, the development of key concepts, theories or technologies as well as breakthroughs in drug discovery research has been reviewed. Lastly, the current outlook and obstacles in drug discovery studies have been discussed in this article. This review provides an understanding of drug discovery research from a historical perspective and current contexts.